Development of DSSAT CROPSIM-cassava model in Thailand: A review current development - Benjamas Kumsueb (2020)
© 2020, King Mongkut's Institute of Technology Ladkrabang. All rights reserved. Crop Simulation Models (CSM) is necessary for understanding and predicting overall agroecosystem performance for specific purposes. Recently, the DSSAT-CSM model has been applied widely to simulate, evaluate and predict the future particularly the scenario choices of decision-makers. Cassava is the main crop that grows in many parts of Thailand. For getting higher yield and greater economic benefit, the crop should be well management. Thus, the DSSAT-CROPSIM-cassava model was developed and applied in various research works to enhance productivity across a range of biophysical, environmental and economic areas. Various research teams are also trying to explore the site-specific technology, preparing to uncertainty threat for the next future but still on the early stage of development. There is a need for more research, teams and resources to develop this technology for precise and effective recommendations for farmers in the near future.